Vision-related Quality of Life in Korean Glaucoma Patients. Issue 2 (February 2017) - Sung, Kyung Rim; Chun, Yeoun Sook; Park, Chan Kee; Kim, Hwang Ki; Yoo, Chungkwon; Kim, Yong Yeon; Park, Ki Ho; Kim, Chan Yun; Choi, Kyu-Ryong; Lee, Kyoo Won; Han, Seungbong; Kim, Chang-sik
Abstract : Purpose of the Study: The purpose of the study was to evaluate vision-related quality of life in Korean glaucoma patients and to explore the associated factors. Methods: A total of 907 glaucoma patients were recruited from the prospectively designed LIGHT (Li fe quality of the g laucoma patient wh o underwent t reatment) study organized by the Korean Glaucoma Society. Basic questionnaire that included items related to socioeconomic status, comorbidity, and lifestyle, and the validated Korean version of the 25-item National Eye Institute Visual Function Questionnaire (NEI VFQ-25) were collected. The Rasch score, a logit-based interval scale estimate to summarizing the NEI VFQ-25 responses, was calculated. The univariate and multivariable regression models were used to evaluate associations between the Rasch score and variables. Results: The mean patient age was 58.1±14.1 years, visual field mean deviation (VF MD) of the better and worse eyes was −4.92±6.14 and −9.77±8.31 dB, binocular-integrated VF (IVF) MD was −3.55±5.31 dB, respectively. The lower NEI VFQ-25 Rasch score showed a significant association with the presence of other ocular diseases ( P =0.020), a high school level of education or less [vs. university ( P =0.006), vs. graduate school or higher ( P =0.019)], an anxious personality [vs. a moderate personality ( P <0.001), vs. a relaxed personality ( P <0.001)], the number of glaucoma medications in use ( P =0.049), worse eye visual acuity ( P <0.001), and IVF MD ( P <0.001). Conclusions: Visual function parameters are important for the vision-related quality of life of Korean glaucoma patients, notably for worse eye visual acuity and IVF MD. However, social factors, self-assessed personality, and treatment-related issues are also substantial predictors of overall life quality.